2018
DOI: 10.1016/j.celrep.2018.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Specific Labeling of Stem Cell Activity in Human Colorectal Organoids Using an ASCL2-Responsive Minigene

Abstract: SummaryOrganoid technology provides the possibility of culturing patient-derived colon tissue and colorectal cancers (CRCs) while maintaining all functional and phenotypic characteristics. Labeling stem cells, especially in normal and benign tumor organoids of human colon, is challenging and therefore limits maximal exploitation of organoid libraries for human stem cell research. Here, we developed STAR (stem cell Ascl2 reporter), a minimal enhancer/promoter element that reports transcriptional activity of ASC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 39 publications
2
44
0
Order By: Relevance
“…This is all consistent with a role for PLAGL2 in the direct transcriptional activation of ASCL2 , as previously demonstrated in intestinal organoids and CRC cell lines [20]. However, to quantitatively gauge the impact on ASCL2 activity in CRC cell lines we used the ASCL2 reporter [38], adapted for transposon-mediated expression of tdTomato (STAR-tdT, Fig. 5D).…”
Section: Resultssupporting
confidence: 79%
“…This is all consistent with a role for PLAGL2 in the direct transcriptional activation of ASCL2 , as previously demonstrated in intestinal organoids and CRC cell lines [20]. However, to quantitatively gauge the impact on ASCL2 activity in CRC cell lines we used the ASCL2 reporter [38], adapted for transposon-mediated expression of tdTomato (STAR-tdT, Fig. 5D).…”
Section: Resultssupporting
confidence: 79%
“…HNF4G is highlighted in red. Average fold change is calculated from the colorectal tumor progression models and colorectal cancer patients reported in Oost et al (). Transcription factors ranked by their normalized enrichment score in the promoters of significantly downregulated genes ( P < 0.001) in the STAR‐positive samples from (A) were shown. Normalized enrichment score (NES) and motif association were determined in iRegulon (Janky et al , ). Genome browser windows over the complete Hnf4a locus showing all data and all used transcript databases.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the relevance of our findings for human biology and disease, we analyzed cancer stem cell (CSC) transcriptomes from patient‐derived and CRISPR‐engineered colorectal cancer organoids (Oost et al , ) for evidence of regulation by Hnf4g. Strikingly, Hnf4g is one of the most downregulated transcription factors in these CSCs (Fig EV4A).…”
Section: Resultsmentioning
confidence: 99%
“…The organoid technology is continuously improving, and very recently it was possible to obtain the labeling of stem cells in normal, benign and malignant tumor organoids of the human colon, thus offering a unique tool for the study of the contribution of intestinal stem cells to normal and tumoral development [ 498 , 499 ]. Importantly, one of these studies reported an orthoptic xenograft system for human colon organoids, enabling stable reconstruction of the human colon epithelium in vivo and using lineage tracing coupled with CRISP-Cas9, it was possible to demonstrate the self-renewal and multipotency of LGR5 + stem cells [ 499 ].…”
Section: Discussionmentioning
confidence: 99%